6x-9=3x+6x

Simple and best practice solution for 6x-9=3x+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-9=3x+6x equation:


Simplifying
6x + -9 = 3x + 6x

Reorder the terms:
-9 + 6x = 3x + 6x

Combine like terms: 3x + 6x = 9x
-9 + 6x = 9x

Solving
-9 + 6x = 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-9 + 6x + -9x = 9x + -9x

Combine like terms: 6x + -9x = -3x
-9 + -3x = 9x + -9x

Combine like terms: 9x + -9x = 0
-9 + -3x = 0

Add '9' to each side of the equation.
-9 + 9 + -3x = 0 + 9

Combine like terms: -9 + 9 = 0
0 + -3x = 0 + 9
-3x = 0 + 9

Combine like terms: 0 + 9 = 9
-3x = 9

Divide each side by '-3'.
x = -3

Simplifying
x = -3

See similar equations:

| 6-3b=-2-4b | | -2.3-6.6=-12.2-3.9 | | 3(3x-1)=4(3x-1) | | .10y-5=15 | | 10d+4+d=180 | | 45-3.5x=25 | | Y=4x-x-11 | | 16+.15x=.25x | | 14x-9=8+21x | | 13p-6=33 | | -9m-9=4 | | 30526-x=155528 | | 3(x+8)+14=2 | | 180=8x+120+7x | | 5b+15n=50 | | 6-.5x=10 | | -3y-9(3y-5)=-6+7(-7-y) | | 3x^2-13x-66=0 | | x+20+x-15+x-45=180 | | (0.6x^4)(0.2x^6)= | | 45+.25x=40+.30x | | 2(y-8)=6y-28 | | 40.25x=40+.30x | | .6x-6=7.2 | | 7u+4=3(u-4) | | 3(2x+4)=4+6x+12 | | -2(w+6)=-4w-16 | | Y-X=V | | 42=13+x+12 | | 17.50(x+400)=315 | | N-8n= | | 12+x+7=26 |

Equations solver categories